The relationship between ApoE, TNFA, IL1a, IL1b and IL12b genes and HIV-1-associated dementia - Pemberton, L.; Stone, E.; Price, Patricia; Van Bockxmeer, F.; Brew, B. (Blackwell Publishing Ltd, 2008)
Objectives: Host genetic factors implicated in AIDS dementia complex (ADC) were studied. Methods: DNA from ADC patients (n = 56), unselected HIV-seropositive patients (n = 112, 171, 185 and 204) and HIV-seronegative controls (n = 204, 60, 60, 96 and 624) were typed for polymorphic loci in genes encoding tumour necrosis factor (TNF)-a, interleukin (IL)-1a, IL-1ß, IL-12 and Apolipoprotein E (ApoE). Diagnosis of ADC was based on neurological symptoms, signs and neuroimaging findings with other causes of dementia excluded. Patients selected had ADC stage =1 and CD4 counts of <500 cells/µL. Results: Allele 2 of TNFA-308 was more common in ADC patients compared to HIV-positive or HIV-negative controls (P = 0.005, 0.024). No other differences between ADC patients and control groups were significant. Meta-analyses confirmed these results. Conclusions: This study suggests that TNFA-308 allele 2 or an allele in linkage disequilibrium with this locus influences ADC. © 2008 British HIV Association.